2016
DOI: 10.14336/ad.2016.0325
|View full text |Cite
|
Sign up to set email alerts
|

Low Normal TSH levels are Associated with Impaired BMD and Hip Geometry in the Elderly

Abstract: Subclinical hyperthyroidism is known to be associated with the risk of fractures in elderly people. However, there are few studies assessing whether low normal thyroid-stimulating hormone (TSH) levels affect bone density and geometry. Here, we aimed to assess the influence of the TSH level on bone mineral density (BMD) and geometry in elderly euthyroid subjects. This was a cross-sectional cohort study. A total of 343 men and 674 women with euthyroidism were included and analyzed separately. The subjects were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
1
13
0
2
Order By: Relevance
“…In this cohort, we found independent and additive association of red blood cell distribution width with morphometric vertebral fracture 29. A low thyroid-stimulating hormone level reflecting subclinical thyrotoxicosis was associated with low bone mass and impaired hip geometry 30. In overall, we sought to establish the value of newly emerging concept, dysmobility syndrome and novel biomarkers of musculoskeletal health in this cohort, which need to be continued in further studies.…”
Section: Cohort Descriptionmentioning
confidence: 80%
“…In this cohort, we found independent and additive association of red blood cell distribution width with morphometric vertebral fracture 29. A low thyroid-stimulating hormone level reflecting subclinical thyrotoxicosis was associated with low bone mass and impaired hip geometry 30. In overall, we sought to establish the value of newly emerging concept, dysmobility syndrome and novel biomarkers of musculoskeletal health in this cohort, which need to be continued in further studies.…”
Section: Cohort Descriptionmentioning
confidence: 80%
“…The National Health and Nutrition Examination Survey (NHANES) has further shown that the odds ratio for correlations between TSH and bone mass ranged between 2 and 3.4 (Morris 2007). Elderly women with low-normal TSH levels (in the euthyroid range) have lower BMDs with or without weaker femoral structures (Ding, et al 2016; Lee, et al 2016). Such women also have a high vertebral fracture risk, independent of age, BMD and thyroid hormones (Mazziotti, et al 2010).…”
Section: Tsh and Bone Mass Regulationmentioning
confidence: 99%
“…To obvykle odhalí uzlovou přestavbu, následná scintigrafie přítomnost independentního adenomu nebo uzlovou přestavbu s oblastmi zvýšené aktivity. Zjištění těchto změn ve ŠŽ je podporou při rozhodování o léčbě, zvláště při fibrilaci či jiném typu dysrytmie nebo při průkazu zvý šeného kostního obratu [24]. Subklinická hypertyreóza by měla být léčena především u starších osob [25,26], podáváme tyreostatika v dávce, která normalizuje TSH, ev.…”
Section: Hypertyreózaunclassified
“…Dle současných názorů supresní léčba u ne rizikových osob postačí maximálně 5 let. Dlouhodobá suprese je rizikem pro rozvoj osteoporózy [24].…”
Section: Karcinom šTítné žLázyunclassified